A single mutation affects both N-acetylglucosaminyltransferase and glucuronosyltransferase activities in a Chinese hamster ovary cell mutant defective in heparan sulfate biosynthesis. - Lidholt, K (1992)
Mutants of Chinese hamster ovary cells have been found that no longer produce heparan sulfate. Characterization of one of the mutants, pgsD-677, showed that it lacks both N-acetylglucosaminyl- and glucuronosyltransferase, enzymes required for the polymerization of heparan sulfate chains. pgsD-677 also accumulates 3- to 4-fold more chondroitin sulfate than the wild type. Cell hybrids derived from pgsD-677 and wild type regained both transferase activities and the capacity to synthesize heparan sulfate. Two segregants from one of the hybrids reexpressed the dual enzyme deficiency, the lack of heparan sulfate synthesis, and the enhanced accumulation of chondroitin sulfate, suggesting that all of the traits were genetically linked. These findings indicate that the pgsD locus may represent a gene involved in the coordinate control of glycosaminoglycan formation.